Description of a new species, Tarchius yunnanensis (Coleoptera: Curculionidae: Cossoninae), from China - Omar, Youssef Mohamed; Han, Kyungduk; Zhang, Runzhi (Zootaxa, 2006)
Tarchius yunnanensis sp. nov. is described from Yunnan Province, China. The genus is reported for the first time in China. A key to the species of Tarchius is presented, and illustrations of diagnostic features of the new species are provided.